Energy : the next fifty years. (OECD, 1999)
This publication brings together the papers presented at the meeting organised jointly by OECD and International Energy Agency in 1998 in Paris. Participants discussed the challenges and the likely trends and developments in world energy through 2050; examined the opportunities and constrains posed by likely evolution of key factors such as the geopolitical landscape, new modes of transport and energy technologies, and climate conditions, and they considered, from a multidisciplinary perspective, the range of possible strategic responses.